(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The prevalence of keratitis and corneal ulcers among rheumatoid arthritis (RA) patients with corneal disease is not known for certain, and the features of their clinical manifestations have been not sufficiently studied. Purpose: To retrospectively assess the prevalence and clinical manifestations of keratitis and corneal ulcers in RA patients with corneal disease based on the medical records of patients that were hospitalized at Corneal Pathology Department of the Filatov Institute from January, 2014, through August, 2019. Material and Methods: We have retrospectively examined the medical records of 6627 patients that were hospitalized at Corneal Pathology Department of the institute in the above period of time. Results: Of the 6627 patients that were hospitalized, 82 (or 1.2%) were RA patients with keratitis and/or corneal ulcers. Of these 82 patients aged 37 to 79 years, 23 (28%) were men and 59 (72%) were women. Bilateral corneal lesions were found in 71 (86.6%), and unilateral corneal lesions, in 11 (13.4%) of the 82 study patients, with 153 eyes totally included in the study. Punctate or filamentary keratitis was found in 90 (58.8%) eyes. Severe corneal lesions (ulcers or keratoscleromalacia) were found in 63 (41.2%) eyes. Of the 82 RA patients with corneal lesions of the current study, 39 (47.6%) did not receive basic therapy for RA, and exhibited the most severe corneal lesions. Conclusion: Patients with RA need to be systematically seen by an ophthalmologist and a rheumatologist. The absence of treatment with basic therapy for RA can cause ocular complications. A patient with RA needs to be treated for any corneal lesion at a tertiary care center where a required surgical procedure can be timely performed. The success of treatment for corneal lesions in a RA patient requires a set of treatment measures, and adequate basic therapy for RA is a necessary component of this set.